Effect Of Irrigation On Harvesting Time And Yield In Mango (Mangifera indica L.) (Bangladesh Journal of Agricultural Research, 2013)
An experiment was carried out at the BAU Germplasm Centre, Department of Horticulture, Bangladesh Agricultural University, Mymensingh to investigate the effect of irrigation on harvesting time, yield and quality attributes of mango cv. BARI Aam -3 (Amrapali) during the period from September 2005 to July 2006. There were seven treatments in the experiment viz., Irrigation at 15th October, Irrigation at 15 October and 15 November, Irrigation at 15th of each month starting from October and continued up to December, Irrigation at 15th of each month starting from October and continued up to January, Irrigation at 15th of each month starting from October and continued up to February, Irrigation at 15th of each month starting from October and continued up to March and Control (no irrigation). The plants those were irrigated twice on 15 October and 15 November exhibited the highest number of panicles per plant (137.33) compared to the lowest number of panicles per plant (9.00) in the treatment where irrigation was given at 15th of each month starting from October and continued up to March. Two irrigations at 15 October and 15 November produced the highest number of fruits per plant (61.67) and irrigation applied on 15th of each month starting from October and continued up to December produced the lowest number of (11.00) fruits. Maximum yield (12.50 kg/plant) was recorded from the plants which were irrigated twice on 15 October and 15 November as compared to minimum yield (2.15 kg/plant) in plants irrigated on 15th of each month starting from October and continued up to December. Irrigation applied on 15th of each month starting from October to March resulted in the longest shelf life (7.28 days) as compared to control (5.63 days). Bangladesh J. Agril. Res. 38(1): 127-136, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15197